Contribución a la biología y mantanimiento de peces marinos ornamentales :usos potenciales de la biodiversidad - Ospina Salazar, Gloria Helena; López Navarro, Johann; Sepúlveda Cárdenas, Sofia; Gómez León, Javier; Sánchez Acevedo, Marisol (INVEMAR, 2018)
2 ed.